MAKNA BATU AKIK DI KALANGAN MASYARAKAT (Studi di Desa Makmur Kecamatan Pangkalan kerinci) - Marse Evalina N; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is to study analyzes the society perceptions about the meanings of agate. This phenomenon is a social phenomenon that occurs in people who have or collect agates and the way they wear an agate. The theory used is the theory of social behavior and a symbolic interactionalism. Data analysis was conducted to address the existing problems in this research is qualitative descriptive approach further analyzed based on the theories in the study and the techniques of data collection in this research is snowball sampling where the number of informants is 7 people consisting of a leader of the neighborhood (RT), a leadear of the Karang Taruna, one student and four membes of the society. Research result showed the meaning of agate stone has a good meaning to society. Society using an agate as an accessory, but some society use that because of the magical power which are contained in agate stone. Because of that conviction, someone will get a bad image in community.Keywords: The meaning of Agate, social behavior, symbolic interactionalism